PENGARUH PERTUMBUHAN PENJUALAN, DIVIDEND PAYOUT RATIO (DPR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mitra Kartini; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThe purpose of this research are: 1) to find out the Sales Growth (SG) and how it affects to the company’s stock prices of food and beverage companies 2) to understand the influence of Dividend Payout Ratio (DPR) towards the company’s stock prices of food and beverage companies 3) to discover the impact of Debt to Equity Ratio (DER) towards company’s stock prices of food and beverage companies.The population of this research are food and beverages companies that listed on the Indonesia Stock Exchange in 2018. The method that is used to analyze by the multiple linear regression test with a t-test as the hypothesis tester. The result of this research has proved that the Sales Growth (SG) has brought a positive influence and not significantly while the Dividend Payout Ratio (DPR) also has a positive impact and significant. However, the Debt to Equity Ratio (DER) has a negative influence and not significantly.Keywords : Stock Price, Sales Growth (SG), Dividend Payout Ratio (DPR), and Debt to Equity Ratio (DER).